Two new species of Caryodaphnopsis (Lauraceae) from the Magdalena Medio, Colombia, with an updated key for the Neotropical Caryodaphnopsis species - Mendoza Cifuentes, Humberto; Quiroga-Nova, Javier David; Daniel Mauricio, Daniel Mauricio; Ayala-Joya, Melisa; Aymard-Corredor, Gerardo (Instituto de Ecología, A.C., 2023)
Background and Aims: Caryodaphnopsis is a tropical genus with an amphi-Pacific distribution, comprising 19 species, 10 of which Neotropical. Two new species are described from wet forest remnants on the western slopes of the Eastern Cordillera of Colombia, which is part of the Magdalena Medio biogeographical region. Their morphological relationships with Neotropical allied species are discussed.Methods: Descriptions and illustrations of both new species were based on collections from the Santander and Boyacá departments, deposited in the herbaria of the Bogotá Botanical Garden (JBB) and the Universidad Industrial de Santander (UIS). Measurements of vegetative parts and inflorescences were taken from herbarium material. Floral structures and fruits were measured from fresh material preserved in alcohol. Threat categories were proposed according to IUCN criteria.Key results: Caryodaphnopsis carmensis and C. yariguiensis are two species so far known only from the Magdalena Medio, Colombia. Caryodaphnopsis carmensis is unique because of its dense, golden pubescence on vegetative parts, leaves with subcordate base and 14-17 arcuate tertiary veins, located between the first pair of secondary veins. Caryodaphnopsis yariguiensis resembles C. fieldii but differs from the latter by the shape of leaves and the stamens with a pair of glands located between the middle portion of filament. Both taxa are proposed as Endangered (EN). An updated key for the Neotropical Caryodaphnopsis species is presented, along with information about their geographic distribution. Conclusions: The two species described are trees that yield one of the finest timbers in the Magdalena Medio and their populations are much reduced. We encourage their cultivation to promote their conservation. With these two new species, Colombia is the country with the greatest diversity of the genus (seven) and the Magdalena Medio has the highest concentration of endemic species (three).